IFIs false promises, workers' losses - Asian Labor Network on International Financial and Trade Institutions/Philippines Chapter (ALNI/P). (Makati Solidarity Center Philippines, 2003)
Introduces international financial institutions such as the World Bank, the International Monetary Fund and Asian Development Bank, and the role they play on implementing globalization policies that has adversely affected the Philippine economy.
"This production was made possible through the support provided by Ford Foundation, under the terms of Grant 1010-0197"--Back cover.
VCD.
Ramon P. Diez, Jr., director ; Rocelle Magpayo, writer.
Keywords: International financial institutions; Globalization -- Economic aspects -- Philippines